PENGARUH LATIHAN HURDLE JUMP DAN LATIHAN LEG PRESS TERHADAP KEMAMPUAN DAYA LEDAK OTOT TUNGKAI PADA MAHASISWA UKM BOLA VOLI IKIP MATARAM TAHU 2019 - Adi Suriatno; Rusdiana Yusuf (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
The problem in this research is stated as; Is there any effect of Hurdle Jump Exercise and Leg Press Exercise toward the Limb Muscle Explosive Power ability on the students of UKM volleyball IKIP Mataram in 2019. The sampling method uses the population study and the total sampling was 12 students of UKM volleyball IKIP Mataram in 2017/2018. The data collection uses documentation, performance test, and vertical jump test. The data analysis technique uses the t-test at 5% significant level. The result showed that the effect of hurdle jump exercise toward ability of limb muscle explosive power is higher than the t-table (5.081 > 2.571). While the limb press exercises on the ability of limb muscle explosive power showed that t-score is higher than t-table (4.164 > 2.571). As a conclusion, there is effect of Hurdle Jump Exercise and Leg Press Exercises toward Limb Muscle Explosive Power Ability on the students of UKM volleyball IKIP Mataram in 2019.